KENAIKAN BIAYA PENGURUSAN STNK & BPKB TAHUN 2017 DI TINJAU MENURUT PERATURAN PEMERINTAH NOMOR 60 TAHUN 2016 - Larto Larto (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe enactment of Government Regulation No. 60 of 2016, there is an increase in tariffs for a number of vehicle administration costs, such as vehicle registration, BPKB, and TNKB as well as the addition of type C license I and C II. Driving License (SIM) C I is for vehicles with engine capacity of 250 cc and SIM C II for vehicles with engines more than 500 cc. The cost of issuance of STNK is 3 times higher than before. As for the making of new SIM, SIM A, SIM B I, and B II are charged Rp. 120.000.Sedangkan SIM C, C I, and C II costs Rp. 100.000. SIM D and SIM D I charged Rp. 50,000. The increase also occurs in the issuance of Motor Vehicle Identity Number with an increase of 100 percent or twice, for two-wheeled vehicles or three costs to Rp. 60,000 from the previous Rp. 30,000, and four wheels to Rp. 100,000 from the previous fee of Rp. 50,000. The biggest increase occurred in the issuance of Book Owners of Motor Vehicles (BPKB), for two wheels to Rp. 225,000 from the previous Rp. 80,000 while four or more wheels to Rp. 375,000 from the previous Rp. 100,000. Regulation of Minimum Service Standards (SPM) as a reference for the Regional Revenue Service apparatus in providing PKB and BBN-KB services to the Taxpayers and to issue official letters required by the recipients of service, in order to be evaluated by the Governor of East Kalimantan as the constituent elements of SAMSAT and or even reviewed Back, in accordance with the needs of the community as the recipient of services in accordance with the expected. In order to raise the regional revenue, UPTD Revenue Service of East Kalimantan Province in Samarinda can play an active role in managing regional income sources in their working area. UPTD officers can be more observant in monitoring, registering and simultaneously collecting tax objects that are still delinquent and have not been monitored and recorded, because there are still many motor vehicle arrears that do not pay taxes and BBN-KB. Samsat Joint Office Service involves 3 (three) institutions, namely Dina Regional Income (Dispenda), Directorate of Traffic Police (Ditlantas Polda) and PT Jasa Raharja (Persero). These three agencies work together to serve the community and take shelter under one roof or one office called the Single Administration System Under One Roof (Samsat). Before the samsat, people must go to these three institutions in different places, so it takes time and energy and this is very perceived inefficient and burdensome society. Mechanism of arrangement and Arrangement of Increase Cost at STNK & BPKB is to improve the level and comfort of society in public service done by Police.Keywords: Vehicle Tax, Levy